Business evaluation of Pangasionodon hypophthalmus nursery in Sukamandijaya Village, Subang - Budiardi, Tatag; Rolin, Febrina; Hadiroseyani, Yani (Indonesian Society of Scientific Aquaculture (ISSA), 2014)
ABSTRACT Nursery business of 1-inch Siam-catfish in Sukamandijaya Village has been conducted based on experience and no information was available regarding to its economical efficiency. The purpose of this study was to evaluate the production performance and input optimalization to maximize profit. The methods used in this study was survey with purposive sampling, while production performance asessment was carried out by direct observations. Economic data were analyzed using Cobb-Douglas production function. Number of fish farmer respondens in this survey was 21 respondents. The volume of nursery tanks were about 3,188−9,860 L at stocking density of 15−47 fish/L. The average of absolute length growth, survival, and daily weight growth rate were 2.77±0.19 cm, 56.04±1.07 %, 27.96±1.09 % respectively. Based on the analysis, the optimal input was at the stocking density of 80 larvae/L and sludge worm density of 0.0919 kg/L.Keywords: input optimalization, maximum profit, production performance, nursery, Siam-catfish ABSTRAK Usaha pendederan ikan patin ukuran 1-inci di Desa Sukamandijaya masih berdasarkan pengalaman dan tidak tersedia informasi mengenai efisiensi ekonomi usaha ini. Tujuan penelitian ini adalah mengevaluasi kinerja produksi dan optimalisasi input produksi untuk menghasilkan keuntungan yang maksimal. Survei dilakukan menggunakan metode purposive sampling dan parameter kinerja produksi diperoleh melalui pengamatan langsung. Data ekonomi dianalisis menggunakan fungsi produksi Cobb-Douglas. Jumlah responden pembudidaya pada penelitian ini adalah sebanyak 21 responden. Volume wadah pendederan berkisar 3.188−9.860 L dengan padat tebar berkisar 15−47 ekor/L. Pertumbuhan panjang mutlak rata-rata ikan patin sebesar 2,77±0,19 cm, tingkat kelangsungan hidup sebesar 56,04±1,07 %, dan laju pertumbuhan bobot harian sebesar 27,96±1,09%. Berdasarkan analisis, penggunaan input yang optimal adalah padat tebar 80 ekor/L untuk larva dan pakan berupa cacing sutra dengan kepadatan 0,0919 kg/L. Kata kunci: optimalisasi input, keuntungan maksimal, kinerja produksi, pendederan, ikan patin